Effect of magnetic field dependent viscosity on the unsteady ferrofluid flow due to a rotating disk - Bhandari, Anupam (Zielona Góra: Uniwersytet Zielonogórski)
The effect of magnetic field dependent viscosity on ferrofluid flow due to a rotating disk is studied in the presence of a stationary magnetic field. The results for velocity profiles for various values of MFD viscosity parameter are shown graphically. These results are compared with the ordinary case when the applied magnetic field is absent. Besides, the shear stress on the wall of the disk and its surface is calculated numerically.
Keywords: ferrofluid; MFD viscosity; rotating risk